Kansas Swine Improvement Association Testing Station - Koch, B.A.; Moyer, W.A. (Kansas Agricultural Experiment Station, 2011)
The seventh group of pigs tested in the Kansas Swine Testing Station completed their test during the 1961-62 winter. The Animal Husbandry Department and the Extension Service cooperation in manging and supervising the station. All expenses incurred in testing are paid by breeders or producers who have pigs tested.
Keywords: Swine; Production data; Stomach ulcers